Analisis Kelayakan Finansial Usaha Jeruk di Kabupaten Karo dan Kabupaten Langkat - Ermanto, Yodi; Lubis, Yusniar; Saragih, Faoza (Universitas Medan Area, 2020)
This study aims to determine the level of income and feasibility of farming orange in Karo and Langkat Districts. This research was conducted in the Bukit Mas Village in the Besitang District and in the Garingging Village in the Brand District of the Karo Regency. Karo Regency is a producer of Matang Oranges or direct consumption, while in Langkat Regency it can be harvested and juice harvested. This research was conducted by the method of Simple Random Sampling with the number of samples taken each 30 farmers who are experienced in the field of citrus plants. Sampling was carried out on April 2018. The method of analysis using the calculation of Net Present Value (NPV) and B / C Ratio. The results showed that the citrus farming in Karo and Langkat Districts was financially feasible because and continued to be developed, referring to the B / C ratio calculation obtained that the two regencies had values greater than 1, where Karo District was 3.13% and Langkat District 4 , 76%.